Enhancing salinity tolerance in wheat: the role of synthetic Strigolactone (GR24) in modulating antioxidant enzyme activities, ion channels, and related gene expression in stress responses - Parisa Jariani; Manijeh Sabokdast; Fatemeh Rajabi; Mohammad Reza Naghavi; Beata Dedicova (Scientific Reports)
Abstract Wheat (Triticum aestivum L.) is a vital global crop; however, its productivity is facing increasing threats from soil salinity, which affects a significant portion of arable land worldwide. This study investigates the potential of synthetic Strigolactone (GR24) to enhance salinity tolerance in wheat by examining its effects on antioxidant enzyme activity, ion homeostasis, and gene expression. Three wheat cultivars with varying salinity resistance (Sistan, Pishtaz, and Tajen) were treated with 10 µM GR24 under two salinity levels (5 and 15 dS/m). Salinity stress was applied from the 3–4 leaf stage to tillering. GR24 significantly enhanced the activities of antioxidant enzymes such as ascorbate peroxidase, catalase, and polyphenol oxidase while reducing guaiacol peroxidase activity. Proline content, potassium levels, and concentrations of chlorophyll and carotenoids were markedly increased, while sodium ion accumulation and indicators of oxidative damage (malondialdehyde, hydrogen peroxide, and electrolyte leakage) were reduced. These effects improved leaf water retention and overall stress resilience. Furthermore, polyphenol oxidase activity highlighted a potential novel pathway of Strigolactone action involving interactions with other phytohormones. Gene expression analysis via real-time PCR revealed that GR24 modulates the transcription of stress-responsive genes, including antiporter genes crucial for maintaining Na+/K + homeostasis and reducing ion toxicity. Among the cultivars, Sistan and Tajen exhibited the most robust responses at a salinity level of 15 dS/m. These findings underscore the potential of GR24 as a promising tool for enhancing wheat performance in saline environments.